Significance of Islamic financial literacy among women entrepreneurs from Islamic perspective - Fatah Yasin, Raudlotul Firdaus; Kassim, Salina; Mahmud, Mek Wok; Diniyya, Aulia Arifatu (2019)
In Islam, women have an important role in promoting the economic growth of a country, including their involvement in entrepreneurship. It acknowledges the positive contribution of women entrepreneur to the sustainable economic development of a country. Nevertheless, there are limitations in mobility and enhancement of women entrepreneurs due to financial illiteracy, especially in the areas where the financial transactions are in line with the Shariah, or better known as Islamic finance. Some are found to be running their business merely relying on personal experience or informal management of entrepreneurship with very little understanding of Islamic finance. This paper aims at discovering the significance of Islamic financial literacy education among women entrepreneur, and its importance in the economic development of the Muslim society. Literature review on existing subjects and interview method will be employed to identify the Islamic perspective on the aspect. The findings of this study provide relevant inputs for, further development of formal Islamic financial literacy in the existing education system.